RAPID ASSESSMENT ON MACRO-MOTH FAUNA AT NUSA BARONG NATURE RESERVE: A LOW DIVERSITY - Hari Sutrisno (The East Java Biological Society, 2007)
Rapid assessment on moth faunas with focus on macro-moths was conducted at Nusa Barong Nature Reserve. The aims of the study were to acquire information of macro-moth diversity and to access the composition of the species at this area by comparing data from Meru Betiri National Park, Sebangau National Park and Busang forest. The results showed that the number of species at Nusa Barong, Meru Betiri, Sebangau and Busang were 47, 75, 97 and 297, respectively. The diversity of macro-moth fauna based on William’s α index at Nusa Barong was the lowest as compared to Meru Betiri National Park, Sebangau National Park and Busang forest, which were 34.58, 65.01, 50.91 and 102.08, respectively. The results also show that the similarity based on Jaccard’s index of the binary comparison varies from 0.029 to 0.089. The highest value was the comparison between Nusa Barong and Meru Betiri while the lowest was the comparison between Nusa Barong and Sebangau. In addition, Pyralidae, Geometridae and Noctuidae were dominant across all sites. At Nusa Barong, only 10 species that have been known their host plants; three of them caused damage to some crops, namely, Conogethes punctiferalis, Cydalima laticostalis and Achaea janata. There might be more species that have not been found during this study as indicated by the species numbers across all sites have not reach a plateau. This study clearly showed us that floral diversity and size of area determined the diversity of macro-moths at Nusa Barong Nature Reserve.